2023
DOI: 10.1007/s40122-023-00527-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Erector Spinae Plane Block in Terms of Analgesic Efficacy in Elderly Patients Undergoing Posterior Lumbar Spine Surgery: A Retrospective, Propensity-Score Matched Study

Abstract: Introduction For preoperative analgesia during a variety of operations, the erector spinae plane block (ESPB) has grown in popularity. However, its effectiveness in lumbar surgery is still unknown. The purpose of this study was to investigate the potential benefits of ESPB in enhancing analgesic efficacy in elderly individuals following posterior lumbar spine surgery. Methods Patients aged 65 years or older who underwent elective posterior lumbar instrumented fusion (wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 29 publications
(30 reference statements)
1
15
0
Order By: Relevance
“…Given the rising prevalence of spine pathologies requiring surgery it is important to address postoperative pain to avoid complications such as transition to chronic pain and reduced mobility. This can place a signi cant economic burden on healthcare systems and individuals due to the costs of medical care, lost productivity, and disability [4,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Given the rising prevalence of spine pathologies requiring surgery it is important to address postoperative pain to avoid complications such as transition to chronic pain and reduced mobility. This can place a signi cant economic burden on healthcare systems and individuals due to the costs of medical care, lost productivity, and disability [4,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the recently published retrospective study that assessed the effectiveness of erector spinae plane block (ESPB) in lumbar spine surgeries [ 1 ], and wish to present our comments on that article.…”
mentioning
confidence: 99%
“…In the abstract, Zhu et al [ 1 ] state that the effectiveness of ESPB in lumbar surgery is still unknown. However, various studies in the last few years have shown the effectiveness of ESPB in lumbar spinal surgeries including systematic review and meta-analyses [ 2 4 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations